The influence of the deposition parameters on the properties of an rf-magnetron-deposited nanostructured calcium phosphate coating and a possible growth mechanism; Surface and Coatings Technology; Vol. 205, iss. 12 - Surmenev R. A. Roman Anatolievich; Surmeneva M. A. Maria Alexandrovna; Evdokimov K. E. Kirill Evgenievich; Pichugin V. F. Vladimir Fyodorovich; Thorsten P. Peitsch; Epple M. K. Mattias Kristian (2011, 2011)
Title screen